Metered‐dose inhalers vs nebulization for the delivery of albuterol in pediatric asthma exacerbations: A cost‐effectiveness analysis in a middle‐income country (2020)
Objectives Although the benefits of albuterol delivered via metered‐dose inhalers with a spacer (MDI+S) have been increasingly recognized, the evidence regarding the cost‐effectiveness of MDI+S compared to nebulization (NEB) is not sufficient, especially in less‐affluent countries, where the clinical and economic burden of the disease is the greatest. The aim of the present study was to evaluate the cost‐effectiveness of MDI+S vs NEB for delivering albuterol for the treatment of pediatric asthma exacerbations. Methods A decision‐analysis model was developed to estimate the cost‐effectiveness of MDI+S vs NEB for delivering albuterol for the treatment of pediatric asthma exacerbations. Effectiveness parameters were obtained from a systematic review of the literature. Cost data were obtained from hospital bills and from the national manual of drug prices in Colombia. The study was carried out from the perspective of the national healthcare system in Colombia, a middle‐income country (MIC). The main outcome of the model was the avoidance of hospital admission. Results For the base‐case analysis, the model showed that compared to NEB, using MDI+S for the delivery of albuterol was associated with lower total costs (US$96.68 vs US$121.41 average cost per patient) and a higher probability of hospital admission avoided (0.9219 vs 0.8900), thus leading to dominance. Conclusions This study shows that in Colombia, an MIC, compared with NEB, the use of MDI+S for delivering albuterol for the treatment of pediatric asthma exacerbations is the preferred strategy because it is associated with a lower probability of hospital admission at lower total treatment costs.